Fracture tooth reattachment - Hassan, Ahmed (International Journal of Dental Research, 2018)
Anterior teeth fractures occur daily, with the main patient demand to restore esthetically the resultant defect.  There is nothing more esthetic than the tooth itself.  Many techniques were described to use the fractured piece to restore this defect in case of accurate fit.  The objective of this article is to summarize these techniques to give the dental practitioners the opportunity to restore the fractured tooth more conservatively and in the same time more esthetically.  Also it throws light on the prevalence and etiology of tooth fracture. Frontal teeth are subjected to traumas more than other teeth in the mouth.  These traumas may lead to tooth fracture with or without pulp involvement.  In attempts to restore the fractured tooth in more esthetic and conservative manner, the fractured piece may be used as a restorative material. This treatment modality has gained increased popularity among dental practitioner due to the continuous development in the adhesive field.  Several techniques were used.  These techniques include, simple reattachment, external chamfer, over contouring, internal dentin bevel, and internal enamel bevel.  All these techniques try to afford the highest fracture resistance accompanied with the least possible tooth preparation.  Combination of two or more technique would result in better performance.Keywords:Bevel, bonding, reattachment, tooth fracture.